"He Just Snapped": Gendered narratives of parents killing their children in the UK press. (10th December 2018) - Niblock, Sarah
Abstract : This article presents findings and recommendations for journalists and educators based on a study of more than 20 years' reporting of infanticide, filicide and family murder–suicide in the United Kingdom's national and regional press. On average, 50 children die each year at the hands of parents in the United Kingdom, and the deaths receive significant media attention. This study finds journalists exhibit a gender-biased trend in their writing depending on the sex of the perpetrator. Furthermore, most media coverage fails to acknowledge that killings by men are often the culmination of long-term domestic violence. Findings suggest news values and sourcing strategies are distorting the true picture and foregrounding tragedy narratives for the predominantly male perpetrators, often blaming women for leading a loving father to "snap". In sharp contrast, mothers who kill are more negatively portrayed. The research finds that crime reporters need training in domestic violence to look beyond simplistic stereotypes.